2021
DOI: 10.1016/j.meegid.2021.105013
|View full text |Cite
|
Sign up to set email alerts
|

A discernable increase in the severe acute respiratory syndrome coronavirus 2 R.1 lineage carrying an E484K spike protein mutation in Japan

Abstract: Three COVID-19 waves in Japan have been characterized by the presence of distinct PANGO lineages (B.1.1. 162, B.1.1.284, and B.1.1.214). Recently, in addition to the B.1.1.7 lineage, which shows 25% abundance, an R.1 lineage carrying the E484K mutation in the spike protein was found to show up to 40% predominance. E484K could be a pivotal amino acid substitution with the potential to mediate immune escape; thus, more attention should be paid to such potential variants of concern to avoid the emergence of mutan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…To determine the phylogenetic background of E484K mutants, we conducted whole-genome sequencing on 112/401 E484K-positive but N501Y-negative mutants. Unlike with Japan, where R.1 has caused considerable community transmission ( 18 ), we detected only 10 R.1 variants, collected in February and March 2021, including 9 with the S255F mutation and belonging to the outbreak clusters from 6 different hospitals. Of the 112 E484K variants, 92% were of B.1.526 and related genetic backgrounds, consistent with the regional epidemiology in the Northeast during this time period ( 12 ).…”
Section: Resultsmentioning
confidence: 90%
“…To determine the phylogenetic background of E484K mutants, we conducted whole-genome sequencing on 112/401 E484K-positive but N501Y-negative mutants. Unlike with Japan, where R.1 has caused considerable community transmission ( 18 ), we detected only 10 R.1 variants, collected in February and March 2021, including 9 with the S255F mutation and belonging to the outbreak clusters from 6 different hospitals. Of the 112 E484K variants, 92% were of B.1.526 and related genetic backgrounds, consistent with the regional epidemiology in the Northeast during this time period ( 12 ).…”
Section: Resultsmentioning
confidence: 90%
“…The mutation was observed even in other lineages, which were isolated from different countries such as Japan (R.1 lineage), Germany, USA (B.1.1.345 lineage), Brazil, etc. (191)(192)(193)(194). Researchers reported that mutation helps in the immune escape event.…”
Section: E484kmentioning
confidence: 99%
“…R.1 lineage containing only the E484K variant was first detected in Japan in November 2020 and partially prevalent in the third wave from October 2020 to February 2021 [ 17 ]. The E484K variant was reported as an escape variant from a monoclonal antibody that neutralizes SARS-CoV-2 [ 18 ].…”
Section: Discussionmentioning
confidence: 99%